M3 Anxiety and Depression in Patients with Breathing Pattern Disorders or Chronic Respiratory Disease. (12th November 2015) - Naylor, SD; Haines, J; Vyas, A; Fowler, SJ
Abstract : Background: Patients that have chronic respiratory disease (CRD) and breathing pattern disorders (BPD) have a higher prevalence of anxiety and depression than the general population. These patients have worse respiratory health outcomes and in addition, their psychological problems are often left undiagnosed and untreated. Little is known about how anxiety and depression varies between CRD and BPD. Methods: This prospective study involved screening patients attending secondary and tertiary respiratory clinics over an eight-week period. Patients were asked to complete the Hospital Anxiety and Depression Scale (HADS), Short Form-12 (SF-12) and St. George's Respiratory Questionnaire (SGRQ). Demographical data and spirometry were also collected. Our primary outcome measure was the difference in these scores between patients with CRD (asthma, bronchiectasis and chronic obstructive pulmonary disease) compared to BPD (vocal cord dysfunction and dysfunctional breathing). Results: 43 patients (21 with CRD and 22 with BPD) completed questionnaires; mean (SD) age 55 (17) yrs, 32 female. The overall prevalence of borderline anxiety was 17% and clinically significant anxiety 37%. The overall prevalence of borderline depression was 15% and clinically significant depression 29%. Of the patients with CRD, 29% had anxiety and 29% depression. In the BPD cohort, anxiety and depression were found in 45% and 30% of patients respectively. The difference between these groups was not statistically significant (anx: P = 0 .42; dep P = 0 .19). Independent predictors for anxiety and depression were higher SGRQ (anx: P = 0 .001; dep: P < 0 .0001), lower SF-12 Mental (anx: P < 0 .0001; dep: P < 0 .0001) and Physical (anx: P = 0 .042; dep: P = 0 .0027) Health Composite Scores, and lower FEV1 % predicted (anx: P = 0 .0043; dep: P = 0 .016). Conclusions: Anxiety and depression are present in a significant numbers of individuals in both CRD and BPD, with no difference between these groups, so efforts should be made to screen for psychological problems in patients with both CRD and BPD. Worse respiratory function and more symptoms are important contributing factors to patients' risk of anxiety and depression.